Anthem Settlement Holds Lessons on Data Breaches, Costs. - AHC MEDIA (Healthcare Risk Management, 2018)
Anthem's recent $115 million settlement — one of the largest ever in a consumer data breach — shows how costly a breach can be for a healthcare organization. Risk managers should remember that even a much smaller breach could be financially devastating.